(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: This study examined toxic effect of a member of the macrolide antibiotic family, erythromycin, on the levels of certain enzymes, namely glutathione (GSH) and catalase (CAT), and investigated the protective role of Vitamin C in mitigating its toxicity in male albino mice (Mus musculus). Materials and Methods: A total of 25 male albino mice were used in the experiment and divided into five groups. The first group served as the control. The second and third groups (treatment groups) were administered erythromycin at doses of 15 mg/kg and 30 mg/kg, respectively. The fourth and fifth groups (protective groups) were given Vitamin C at a dose of 100 mg/kg along with erythromycin. The experiment lasted for 14 days. Results: A significant decrease in GSH and CAT levels was observed in the treatment groups: (31.2 ± 0.3 µmol/L, 402.9 ± 15.08 U/L) for the second group and (32.1 ± 0.1 µmol/L, 374.9 ± 17.9 U/L) for the third group, which received erythromycin at doses of 15 mg/kg and 30 mg/kg, respectively, compared to the control group at a significance level of (P≤0.05). However, the fourth and fifth groups, which were administered vitamin C along with erythromycin, exhibited an increase in enzyme levels, with no significant differences compared to the control group at the same significance level. Conclusion: Erythromycin exerts a dose-dependent toxic effect on the levels of glutathione and catalase enzymes in the serum of albino mice. Additionally, vitamin C has a protective role in reducing the drug’s toxicity when administered together.